2018
DOI: 10.3390/ijerph15092003
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Supplementation Reduces the Symptoms of Upper Respiratory Tract Infection during Winter Training in Vitamin D-Insufficient Taekwondo Athletes: A Randomized Controlled Trial

Abstract: Vitamin D insufficiency may be associated with increased risk of upper respiratory tract infection (URTI) in athletes. This study examined the effects of vitamin D3 supplementation on salivary immune functions and symptoms of URTI in vitamin D-insufficient taekwondo athletes. Twenty-five male taekwondo athletes, aged 19–22 years with vitamin D insufficiency [serum 25-hydroxyvitamin-D concentrations (25(OH)D, 31.3 ± 1.39 nmol/L)], participated in this study. They were randomized to receive 5000 IU/day of vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 46 publications
(71 reference statements)
2
38
1
Order By: Relevance
“…It is possible that the lack of variation in 25(OH)D concentration between groups may have reduced the ability to detect a relationship between vitamin D and URTI episodes, which is consistent with the findings reported by Scullion et al [39]. It should be noted that the reduction in URTI risk achieved via vitamin D supplementation appears to be greater in cohorts with severe vitamin D deficiency [17,40,41], which may also explain the lack of association between 25(OH)D concentration and URTI in the current study.…”
Section: Discussionsupporting
confidence: 77%
“…It is possible that the lack of variation in 25(OH)D concentration between groups may have reduced the ability to detect a relationship between vitamin D and URTI episodes, which is consistent with the findings reported by Scullion et al [39]. It should be noted that the reduction in URTI risk achieved via vitamin D supplementation appears to be greater in cohorts with severe vitamin D deficiency [17,40,41], which may also explain the lack of association between 25(OH)D concentration and URTI in the current study.…”
Section: Discussionsupporting
confidence: 77%
“…A prior study suggested that the overall infection rate increased significantly during RA onset, and the antibacterial defense mechanism was defective (33). Recently, authors reported that VitD supplementation effectively reduced the incidence of acute cellular rejection and infection (34,35), upper respiratory infection (36,37) and acute respiratory infections (36,38). However, we obtained different results compared with the above studies.…”
Section: Discussioncontrasting
confidence: 65%
“…That vitamin D should play a role in COVID-19 is not unexpected, since there has been believed to be a link between vitamin D deficiency and respiratory disease for over 100 years. Observational studies have reported independent associations between low serum concentration of 25hydroxyvitamin D and susceptibility to acute respiratory tract infections [40]. Vitamin D deficiency is associated with an increased risk of the acute respiratory distress syndrome (ARDS), intensive care admission, and mortality in patients with pneumonia [41].…”
Section: The Role Of Vitamin D As a Possible Modulator Of Susceptibilmentioning
confidence: 99%